Regímenes complementarios de jubilación en el Perú: ¿una opción paralela? - Abanto Revilla, César (2015)
In Peru, since the end of the year 1992, there is a mixed retirement model which consists of a public system – integrated by the members of the armed and police forces (Decree Law 19846), public officials (Decree Law 20530), diplomatic officials (Supreme Decree 065-2009-RE) and the National Retirement System (Decree Law 19990) - and, in parallel, a private model, namely, the Private Retirement System (SPP – Sistema Privado de Pensiones) of the Retirement Fund Administrators (AFP – Administradores de Fondos de Pensiones) (Decree Law 25897). Due to the extent that several factors have affected the normal development of the public retirement systems, they have been tried to be replaced by the Chilean private model of 1980. However, the financial crises have revealed that this mechanism also has weaknesses, especially by their intimate connection with the volatility of the financial and stock markets, which have led to test alternative formulas. In some cases, these have been aimed towards supplementary retirement models, that is, the creation of retirement funds which are designed to provide additional benefits to those recognized by the existing mandatory systems.